2003
DOI: 10.1002/cjg2.415
|View full text |Cite
|
Sign up to set email alerts
|

Amplitude and Anisotropy of Apparent Resistivity Changing of Big Models during Shear and Frictional Slipping

Abstract: The models of uniform and non‐uniform media of 1m×1m×0.3m were made with quartz sand and river sand blend cement under mould pressing. The amplitudes and anisotropic features of apparent resistivity changing were observed at different positions and different orientations on measured planes of the model during shear and frictional slipping. The results of experiments are as follows. The resistivity change is related to the position of measurement lines that are combined with four electrodes. The amplitudes of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2008
2008
2012
2012

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…For example, Mao et al [7,8] used the resistivity data measured along E-W and N-S trending measuring lines in studying the changes in the degree of earth resistivity anisotropy during the course of earthquake preparation. Chen et al [22][23][24][25] designed four measuring lines in studying the changes of apparent resistivity anisotropy in lab. In this paper, we arranged three measuring lines intersecting at point O (Figure 1), which allowed us to study the changes in apparent resistivity anisotropy at point O with pressure and depth.…”
Section: Apparent Resistivity Anisotropymentioning
confidence: 99%
See 2 more Smart Citations
“…For example, Mao et al [7,8] used the resistivity data measured along E-W and N-S trending measuring lines in studying the changes in the degree of earth resistivity anisotropy during the course of earthquake preparation. Chen et al [22][23][24][25] designed four measuring lines in studying the changes of apparent resistivity anisotropy in lab. In this paper, we arranged three measuring lines intersecting at point O (Figure 1), which allowed us to study the changes in apparent resistivity anisotropy at point O with pressure and depth.…”
Section: Apparent Resistivity Anisotropymentioning
confidence: 99%
“…The striking changes in electrical resistivity and its anisotropy were widely observed before earthquake, mine earthquake, volcanic activities, and geologic motions [1][2][3][4][5][6][7][8][9][10][11][12]. In order to address the change characteristics of resistivity and its anisotropy, many investigators conducted a plenty of experiments on rock samples under compression and during fracture, shear, and frictional sliding in lab [13][14][15][16][17][18][19][20][21][22][23][24][25] and theoretic studies [26][27][28][29][30]. Experimental results reported by Brace et al [13] and Brace and Orange [14][15][16] in lab showed that striking changes in electrical resistivity were observed for a variety of igneous and sedimentary crystalline rocks when water-saturated crystalline rocks were stressed to fracture.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation